Progress of Adipokines in the Female Reproductive System: A Focus on Polycystic Ovary Syndrome - Chen, Peipei; Jia, Rui; Liu, Yuanyuan; Cao, Mingya; Zhou, Liang; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Adipose tissue, one type of loose connective tissue in the human body, maintains the primary task of energy storage. Adipose tissue is not only an energy reservoir but also plays a vital role as the largest endocrine organ of the whole body via releasing a variety of adipokines, which participate in many pathophysiological processes, such as energy metabolism regulation, glucose and lipid metabolism, and inflammation. Polycystic Ovary Syndrome (PCOS) is a disorder that mainly involves the female reproductive system, affecting women of childbearing age particularly. Insulin resistance (IR) and hyperandrogenemia (HA) have been implicated as a critical link involving the etiology and outcome of PCOS. A great deal of studies have bridged the gap between adipokines (such as Adiponectin, Chemerin, Metrnl, Apelin, Resistin, Visfatin, Leptin, Vaspin, Lipocalin 2, and Omentin) and reproductive fitness. In this review, we will focus on the adipokines’ functions on PCOS and come up with some points of view on the basis of current research.